Development and characterization of activated hydrochars from orange peels as potential adsorbents for emerging organic contaminants - Fernandez, Maria Emilia (2015)
Activated hydrochars obtained from the hydrothermal carbonization of orange peels (Citrus sinensis) followed by various thermochemical processing were assessed as adsorbents for emerging contaminants in water. Thermal activation under flows of CO2 or air as well as chemical activation with phosphoric acid were applied to the hydrochars. Their characteristics were analyzed and related to their ability to uptake three pharmaceuticals (diclofenac sodium, salicylic acid and flurbiprofen) considered as emerging contaminants. The hydrothermal carbonization and subsequent activations promoted substantial chemical transformations which affected the surface properties of the activated hydrochars; they exhibited specific surface areas ranging from 300 to ∼620 m2/g. Morphological characterization showed the development of coral-like microspheres dominating the surface of most hydrochars. Their ability to adsorb the three pharmaceuticals selected was found largely dependent on whether the molecules were ionized or in their neutral form and on the porosity developed by the new adsorbents.